The fallacy of the fiscal theory of the price level - one last time - Willem H. Buiter; Anne C. Sibert (Kiel Institute for the World Economy (IfW), 2017)
There have been attempts to resurrect the fiscal theory of the price revel (FTPL). The original FTPL rests on a fundamental compounded fallacy: confusing the intertemporal budget constraint (IBC) of the State, holding with equality and with sovereign bonds priced at their contractual values, with a misspecified equilibrium nominal bond pricing equation, and the "double use" of this IBC. This fallacy generates a number of internal inconsistencies and anomalies. The issue is not an empirical one. Neither does it concern the realism of the assumptions. It is about flawed internal logic. The issue is not just of academic interest. If fiscal policy authorities were to take the FTPL seriously, costly policy accidents, including sovereign default and hyperinflation, could be the outcome. Interpreting the FTPL as an equilibrium selection mechanism in models with multiple equilibria does not help. Attempts by Sims to extend the FTPL to models with nominal price rigidities fail. The attempted resurrection of the FTPL fails. It is time to bury it again - for the last time.
Keywords: E31; E40; E50; E58; E62; H62; H63; 330; fiscal theory of the price level; intertemporal budget constraint; equilibrium bond pricing equation; monetary and fiscal policy coordination; equilibrium selection; fiscal dominance